Dicer-like Proteins Regulate the Growth, Conidiation, and Pathogenicity of Colletotrichum gloeosporioides from Hevea brasiliensis - Wang, Qiannan; An, Bang; Hou, Xingrong; Guo, Yunfeng; Luo, Hongli; He, Chaozu (Frontiers in Microbiology, 2018)
Colletotrichum gloeosporioides from Hevea brasiliensis is the hemibiotrophic fungi which could cause anthracnose in rubber trees. Dicer like proteins (DCL) were the core enzymes for generation of small RNAs. In the present study, the knocking-out mutants of two dicer like proteins encoding genes of C. gloeosporioides were constructed; and functions of two proteins were investigated. The results showed that DCL play important roles in regulating the growth, conidiation and pathogenicity of C. gloeosporioides; and there is a functional redundancy between DCL1 and DCL2. Microscopy analysis and DAB staining revealed that loss of penetration ability into the host cells, instead of the decreased growth rate, was the main cause for the impaired pathogenicity of the ∆Dcl1∆Dcl2 double mutant. Proteomics analysis suggested that DCL proteins affected the expression of functional proteins to regulating multiple biological processes of C. gloeosporioides. These data lead to a better understanding of the functions of DCL proteins in regulating the development and pathogenesis of C. gloeosporioides.